(untitled) (MAUSAM, 1969)
This paper reports the computed values of conversion factor for obtaining the values of mean monthly daily total solar radiation received on tilted surfaces from the available records on horizontal surfaces for four widely separated Indian cities, The angles of tilt selected are normally used for fiat plate collectors, during various seasons of the year o Measured value of the ratio of diffused to total solar radiation have been used for Delhi and Poona, and computed values for Calcutta and Madras. Liu and Jordan’s formulae based on the assumption of an isotropic sky have been employed.